EFFICACY AND SAFETY OF IVABRADINE AND BISOPROLOL IN PATIENTS WITH ISCHEMIC HEART DISEASE: RESULTS OF COMPARATIVE RANDOMIZED OPEN STUDY - R. D. Kurbanov; A. O. Kan; F. M. Bekmetova; A. B. Shek (Рациональная фармакотерапия в кардиологии)
Aim. To study influence of ivabradine as compared with bisoprolol on clinical and hemodynamic indices, exercise tolerance, endothelial function, quality of life (QL) and erectile function in patients with ischemic heart disease. Material and methods. 60 males with stable angina pectoris were enrolled into comparative randomized crossover open study. One half of patients randomly received ivabradine during 14 days with replace it with bisoprolol for the next 3 months, another half of patients received compared drugs in the reverse order . Treadmill-test and flow-mediated dilatation (FMD) test were performed initially and after 14 days of treatment with each drug. QL and erectile function were evaluated after 3 months with Seattle Angina Questionnaire (SAQ) and International Index of Erectile Function (IIEF-5), respectively. Results. Heart rate reduced by 16.7±4.6 (p<0.005) and 16.4±4.8 bpm (p<0.005) after 2 weeks of treatment with bisoprolol and ivabradine, respectively. 30 (50.0%) and 31 (51.7%) patients treated with bisoprolol and ivabradine, respectively , increased exercise tolerance ≥1 min in the treadmill-test. Ivabradine treatment, in comparison with bisoprolol one, was associated by more expressed increase in chronotropic reserve in treadmill-test (p<0.05) and significant improvement of sensitivity coefficient of brachial artery to tension shift in FMD (p<0.005). In patients with endothelial dysfunction bisoprolol (69.4 %) and ivabradine (52.8%) efficacy did not differ significantly. At the same time in patients with normal endothelial functions increase in exercise tolerance ≥1 min in treadmill-test was observed in 50% (p<0.05) and 20.8% of patients treated with ivabradine and bisoprolol, respectively. Both drugs significantly increased QL, and ivabradine improved erectile function (p<0.005) in comparison with bisoprolol. Conclusion. The If-channel inhibitor ivabradine and beta-blocker bisoprolol have a similar antianginal efficacy in patients with stable angina pectoris. Treatment with ivabradine, in comparison with bisoprolol, was associated with improvement of chronotropic reserve in treadmill-test (p<0.05), sensitivity coefficient of brachial artery to tension shift in FMD test (p<0.005) and erectile function (p<0.005).